EFEKTIVITAS E-TICKETING KARTU NON TUNAI PADA BISKITA TRANS PAKUAN BOGOR DI ERA INDUSTRI 4.0 - Agus Hidayat (LPPM STISIP IMAM BONJOL, 2026)
Technological advancements in the Industrial 4.0 era have driven the transformation of payment systems in public transportation, including the implementation of e-ticketing using e-money cards on BisKita Trans Pakuan Bogor. However, the effectiveness of this system is considered low due to its limited usage, restricted number of issuing financial institutions, and the difficulty of reloading balances. Moreover, experts argue that e-money cards are outdated, as smartphone adoption continues to rise alongside innovations in digital payment systems such as QR Code (QRIS). This qualitative study reveals that the adoption of QRIS as an alternative payment method is urgently needed to overcome the limitations of e-money cards and to support the integration of the national digital economy and finance. Keywords: Effectiveness, E-ticketing, Industry 4.0